Rhinophyma: Prevalence, Severity, Impact and Management - Chauhan R; Loewenstein SN; Hassanein AH (Dove Medical Press, 2020)
Ruvi Chauhan, Scott N Loewenstein, Aladdin H Hassanein Indiana University School of Medicine, Department of Surgery, Division of Plastic Surgery, Indianapolis, IN, USACorrespondence: Aladdin H HassaneinIndiana University School of Medicine, Department of Surgery, Division of Plastic Surgery, 545 Barnhill Drive, Suite 232, Indianapolis, IN 46202, USATel +1 317-944-3636Fax +1 317-968-0733Email ahassane@iu.eduAbstract: Rhinophyma is an advanced stage of rosacea affecting the nasal soft tissues and resulting in disruption of the nasal architecture, airway obstruction, and disfigurement of the nasal aesthetic units. Rhinophyma presents with hypertrophy of the nasal soft tissues, erythema, telangiectasias, nodules, and lobules with a bulbous appearance. Significant psychosocial morbidity is associated with the disease. Understanding of this disease has improved and multiple treatment options exist. The article is a review of the literature to evaluate the pathophysiology, clinical presentation, and epidemiology of keywords “rhinophyma” and “rosacea” using an OVID Medline and PubMed search along with a systematic review of outcomes pertaining to treatment of rhinophyma with laser therapy, scalpel excision, and the subunit method using an OVID Medline search. The subunit method has the highest complication and revision rates followed by carbon dioxide laser therapy. Outcomes between carbon dioxide laser and scalpel therapy and electrocautery are equivalent. Scalpel excision is a more cost-effective treatment modality with less post-operative complications; however, it risks poor hemostasis intraoperatively. Patient satisfaction is common post-therapy regardless of the treatment method. Over 89% of patients would recommend undergoing treatment for rhinophyma irrespective of treatment type. Treatment options vary, and choice of treatment can be dependent on practitioner and patients’ treatment goals.Keywords: subunit method, phyma, systematic review